2020
DOI: 10.3390/ijms21061984
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Shields the Periodontal Killer Porphyromonas gingivalis from Recognition by the Host Immune System and Supports the Bacterial Infection of Gingival Tissue

Abstract: Candida albicans is a pathogenic fungus capable of switching its morphology between yeast-like cells and filamentous hyphae and can associate with bacteria to form mixed biofilms resistant to antibiotics. In these structures, the fungal milieu can play a protective function for bacteria as has recently been reported for C. albicans and a periodontal pathogen—Porphyromonas gingivalis. Our current study aimed to determine how this type of mutual microbe protection within the mixed biofilm affects the contacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 79 publications
1
32
0
1
Order By: Relevance
“…were associated with OSCC; increased relative abundances of this fungi were observed in saliva samples from patients with OSCC compared to those taken from healthy individuals and, similarly, in tumoral tissue compared to fibroepithelial polyps [ 82 , 83 ]. A microbial coexistence of C. albicans and a periodontal pathogen P. gingivalis has been described; these two microorganisms have a relationship in which C. albicans shields the P. gingivalis from recognition by the host immune system and, in this way, supports the bacterial infection [ 118 ]. Moreover, C. albicans displays a synergistic interaction with commensal oral streptococci, which can have implications for the pathogenic potential of C. albicans in the oral mucosa [ 119 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…were associated with OSCC; increased relative abundances of this fungi were observed in saliva samples from patients with OSCC compared to those taken from healthy individuals and, similarly, in tumoral tissue compared to fibroepithelial polyps [ 82 , 83 ]. A microbial coexistence of C. albicans and a periodontal pathogen P. gingivalis has been described; these two microorganisms have a relationship in which C. albicans shields the P. gingivalis from recognition by the host immune system and, in this way, supports the bacterial infection [ 118 ]. Moreover, C. albicans displays a synergistic interaction with commensal oral streptococci, which can have implications for the pathogenic potential of C. albicans in the oral mucosa [ 119 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The adhesion regions of Kgp and RgpA participate in the adhesion of red blood cells, while the decomposition of red blood cells and the hydrolysis of hemoglobin mainly depend on the hydrolysis regions of Kgp, RgpA, and RgpB ( Smalley et al, 2007 ; Li et al, 2011 ). In addition, the gingipains of P. gingivalis can interact with the surface proteins of C. albicans to promote the stability of the dual-species biofilm, and can also regulate the host reaction by hydrolyzing the main defense molecules ( Bartnicka et al, 2019 , 2020 ). Therefore, gingipains play an important role in the perpetuation of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of interaction between C. albicans and Porphyromonas gingivalis , a bacterium considered the most important in developing periodontitis [ 81 , 82 ]. In a biofilm model, it has been shown that, in the presence of oxygen, C. albicans creates a protective environment for P. gingivalis [ 81 , 83 ]. To conclude, Candida plays a significant role in oral infections.…”
Section: Clinical Manifestations Of Candidiasismentioning
confidence: 99%